2010
DOI: 10.1021/je100945u
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of 1-Ethyl-3-methylimidazolium Bis(trifluoromethylsulfonyl)imide

Abstract: (p,ρ,T) data of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [EMIM][NTf2] at T = (283.15 to 373.15) K and pressures up to p = 100 MPa are reported with an estimated experimental relative combined standard uncertainty of Δρ/ρ = ± (0.01 to 0.08) % in density. The measurements were carried out with a newly constructed Anton Paar DMA HPM vibration-tube densimeter. The system was calibrated using double-distilled water, methanol, toluene and aqueous NaCl solutions. An empiric equation of state for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 35 publications
5
61
3
Order By: Relevance
“…Thermodynamic properties of ILs, their mixtures, and non-aqueous mixtures containing ILs were reviewed recently by Heintz (2005) and Aparicio (Aparicio et al, 2010). This work is a continuation of our investigations in the fi eld of (p, ρ, T) properties of ionic liquids (Tekin et al, 2007;2009;Safarov and Hassel, 2010;Safarov et al, 2011). Included are the (p, ρ, T) properties of [BMIM] [DCA] at T = (283.15 to 393.15) K, at pressures up to p = 100 MPa, and viscosity measurements at T = (278.15 to 373.15) K, at pressures p = 0.101 MPa.…”
Section: Introductionmentioning
confidence: 68%
“…Thermodynamic properties of ILs, their mixtures, and non-aqueous mixtures containing ILs were reviewed recently by Heintz (2005) and Aparicio (Aparicio et al, 2010). This work is a continuation of our investigations in the fi eld of (p, ρ, T) properties of ionic liquids (Tekin et al, 2007;2009;Safarov and Hassel, 2010;Safarov et al, 2011). Included are the (p, ρ, T) properties of [BMIM] [DCA] at T = (283.15 to 393.15) K, at pressures up to p = 100 MPa, and viscosity measurements at T = (278.15 to 373.15) K, at pressures p = 0.101 MPa.…”
Section: Introductionmentioning
confidence: 68%
“…4a, discrepancies between model prediction and the experimental data of Gu and Brennecke [58] and Harris et al [59] are observed at pressures higher than 1000 bar for Table 6 ARDs of the ePC-SAFT predicted pure-IL densities with respect to the experimental data up to 3000 bar. [49], the error is 0.18% on average. In the case of [C 4 mim][Tf 2 N], it is slightly higher (0.39%).…”
Section: Il-density Prediction Up To 3000 Barmentioning
confidence: 89%
“…The (p, q, T) measurements of [C4mpyr][BF 4 ] were carried out using a new state-of-the-art high pressure-high temperature Anton-Paar DMA HPM vibrating tube densimeter [11,12,[26][27][28]. The vibration tube (length 15 cm, U radius 1 cm, OD 6 mm, ID 2 mm, liquid volume 2 cm 3 ) was made of corrosion resistant and fabricabile material (Hastelloy C-276, nickel-molybdenum-chromiumtungsten alloy).…”
Section: Methodsmentioning
confidence: 99%
“…We studied two ionic liquids with viscosity correction [11,12], where the viscosity corrections dependence on temperature and pressure were (q HPM À q)/q HPM = (0.01 to 0.15)%. The corrected density using viscosity values are smaller than not-corrected density values.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation